Physical activity and ageing: The role of physiotherapy in promoting healthy ageing - Shane Naidoo; Nirmala Naidoo (South African Journal of Physiotherapy)
Background: The global rise in the older population, especially in sub-Saharan Africa, has heightened the impact of non-communicable diseases (NCDs), responsible for 74% of global deaths and the leading cause for years lived with disability. Physical activity (PA) has proven to manage NCDs; however, 80% of older adults in sub-Saharan Africa engage in low-to-moderate PA levels.